Evolution of Forensic Accounting in Russia as a Special Branch of Economic Knowledge - Zhanna A. Kevorkova (Учёт. Анализ. Аудит, 2019)
Object. The need for forensic accounting expertise emerged over time with the development and changes in technology, society and economy. The article describes the evolution of forensic accounting in Russia and identifies the main periods of its formation, as well as the practical importance of forensic accounting as a tool of detecting the negative phenomena and fraud for each period. Goal. The essence of forensic accounting as a science is considered not only through the definition, economic content, goals and objectives, but also by taking into account the historical aspects to identify its characteristic features in every period of evolutionary development. A large number of controversial provisions related to this issue require scientific research. Methodology. The results of fundamental publications of Russian and foreign scientists in the field of forensic accounting and law make the methodological basis of the research. The study of evolution in forensic accounting through the application of methods of analysis, analogy, concretization and comparison allows identifying its positive aspects, which now can be used in the theory and practice of making accounting expertise. The article emphasizes that at each stage the focus of forensic and accounting examination and the usefulness of the materials obtained have always been and will be demanded by those who want the expertise. The use of forensic accounting as a tool for detecting the signs of economic crimes in the economic entities is associated with certain difficulties, since when making expertise not only the legal, but increasingly the economic aspect should be considered. Results. A study of the historical development of forensic accounting allows us to identify not only its strength but also its weaknesses in each period. The results obtained can serve as a basis for the development of the main directions of improvement of forensic accounting as a field of scientific study. Conclusions. The results of the study of the evolutionary development of forensic accounting reveal the existence of problems the solution of which should be aimed at working out special proposals for each stage of its development in order to use forensic accounting as a control tool for detecting signs of offences in the activity of economic subjects.